Book review: Transform plate boundaries and fracture zones, by J.C. Duarte (Ed.), 2019. Elsevier Inc., Amsterdam. 478 pages. Paperback: price €137,55, ISBN 9780128120644. - Stawikowski, Wojciech (Geologos, 2020)
Book review: Transform plate boundaries and fracture zones, by J.C. Duarte (Ed.), 2019. Elsevier Inc., Amsterdam. 478 pages. Paperback: price €137,55, ISBN 9780128120644.